2014
DOI: 10.5751/es-06404-190241
|View full text |Cite
|
Sign up to set email alerts
|

Landowners' perceptions of risk in grassland management: woody plant encroachment and prescribed fire

Abstract: ABSTRACT. Ecologists recognize that fire and herbivory are essential to maintaining habitat quality in grassland ecosystems. Prescribed fire and grazing are typically used on public reserves to increase biodiversity, improve grassland productivity, and control encroachment of woody plants. However, these tools, particularly prescribed fire, have not been widely adopted by private landowners. Fire suppression and prescribed fire are strategies that present competing risks to owners who make management decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…Nevertheless, O'Brien and Wolf 2010 (Brandt et al, online;Pretty and Smith, 2004). Further, we found that when led by knowledge-related constraints, values-related constraints appear more tangible, consistent with Pannell et al (2006) (Harr et al, 2014).…”
Section: Perspectives On Application Of the Values-rules-knowledge Frsupporting
confidence: 67%
See 1 more Smart Citation
“…Nevertheless, O'Brien and Wolf 2010 (Brandt et al, online;Pretty and Smith, 2004). Further, we found that when led by knowledge-related constraints, values-related constraints appear more tangible, consistent with Pannell et al (2006) (Harr et al, 2014).…”
Section: Perspectives On Application Of the Values-rules-knowledge Frsupporting
confidence: 67%
“…Even then, monitoring, eradicating or containing these exotics would require concerted community effort, investment, consensus and support (R) (Marshall et al 2016). Harr et al, 2014;Howden et al, 2008;Pannell et al, 2006;Pelling, 2011) Evidence that local populations are best adapted to local conditions has led to a strong focus on using local provenances (including local species and genotypes) for environmental plantings (Broadhurst et al, 2008). In a changing climate, principles of local provenancing may no longer apply.…”
Section: Conflicting Values and Inadequate Rules Could Results In Highmentioning
confidence: 99%
“…Examples include narrative scenario planning (Swart et al 2004), concept mapping (Harr et al 2014 consider. As these approaches become more mainstream, it is important to select participatory modeling methods based on the community involved in the modeling process, research questions or management goals, and how each tool differs across dimensions such as ease of use with stakeholders, model inputs and outputs, and the degree of spatial or temporal extent.…”
Section: Discussionmentioning
confidence: 99%
“…Juniper invasion also reduces wildfire suppression potential and has been implicated as a major reason for the increase in the frequency and size of wildfires at the wildland-urban interface (Pierce and Reich, 2010). Fire, especially uncontrolled wildfire, is perceived negatively, even though the natural fire regime provides an ecosystem service in controlling cedar invasions (Morton et al, 2010;Harr et al, 2014). The transition between grasslands and cedar forests is non-linear, and both system regimes are generally resilient to change (Pierce and Reich, 2010).…”
Section: Invasive Red Cedar and Tradeoffs Between Ecosystem Servicesmentioning
confidence: 99%
“…This generally involves experimental approaches such as cutting, fire, herbicides, grazing domestic goats and combinations thereof. The plan recognizes that cedar invasion in the ecosystem is not simply a biological problem, but has as much to do with how people perceive the landscape and structuring processes such as fire (e.g, Morton et al, 2010;Harr et al, 2014). Therefore, the Nebraska Wildlife Action Plan has also provided for scenario-building exercises with a landscape-level group of stakeholders (e.g., ranchers, local communities, land management agencies, local researchers), such that alternative future states of landscapes can be envisioned, and pathways to attain desirable future states are identified collaboratively.…”
Section: Invasive Red Cedar and Tradeoffs Between Ecosystem Servicesmentioning
confidence: 99%